KESANTUNAN BERBAHASA ANAK JALANAN DI KOMUNITAS ANA’TUGU KELURAHAN DOPING - NFN Muhsyanur (Balai Bahasa Sulawesi Tengah, 2016)
Politeness is a very important aspect in forming the language and characters. Languageof street children is one part of the language of a community, which have specialcharacteristics in their usage. It is interesting to study further because of the conditionof language that occurs in the community of street children varies along with the times.One observer of the community street children in Doping village is Ana'Tugucommunity. This study aimed to describe the forms of politeness and impolitenessmaxims used by street children in the Ana'Tugu community in Doping Village. Themethod used is descriptive qualitative method by using the participatory observationtechnique, recording technique and field notes. Analysis of data using a comparativemethod of pragmatics framework. Determination of politeness and unpoliteness basedon indicators derived from the theory of Leech. Results of analysis showed that thereare 44 adherence to the principles of politeness in the conversation of the streetchildren, while the deviation of 4 speech. Data politeness principle consists of sixmaxims, they are tact maxim, sympathy maxim, approbation maxim, generossity maxim,modesty maxim, and agreement maxim. The most common maxims of politeness inconversation among the street children is an agreement and generosity maxim.